Study on Static Characteristics of Annular Array Microporous Aerostatic Bearing - Xiao-Long Zhao; Hao Dong; Ya-Juan Wang; Bo Li (Shock and Vibration)
In this paper, an aerostatic bearing model in the form of microorifice annular array is designed to explore the static performance of aerostatic bearing when the orifice diameter and working air film thickness are of the same order of magnitude. Firstly, the simulation model of the new bearing is established, the pressure distribution of the bearing gas film under the influence of the orifice diameter is analyzed by the CFD method, and the performance of the aerostatic bearing is compared with the traditional toroidal throttling method with the orifice diameter of 0.1 mm; at the same time, the effects of air supply pressure, orifice diameter, and orifice number on the static performance of the bearing under different air film thickness are analyzed; finally, a new bearing is developed, and the simulation results are verified by the experimental test. The results show that when the orifice diameter and the air film thickness are of the same order of magnitude, the maximum stiffness of the aerostatic bearing is significantly improved and the microporous throttled aerostatic bearing is more suitable for the field of high stiffness. The greater the air supply pressure, the greater the bearing capacity and stiffness of the bearing. The number of orifices has an effect on improving the bearing capacity of the bearing, but when the number of orifices is large, the effect will become less obvious. This study can provide a new theoretical reference for the design of aerostatic bearing.